Models for the study of skin wound healing. The role of Nrf2 and NF-κB - Ambrozova, Nikola; Ulrichová, Jitka; Galandakova, Adela (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2017)
Nrf2 and NF-κB transcription factors act in wound healing via their anti-inflammatory and anti-oxidant effects or through the immune response. Studying this process is a matter of some importance given the high cost of wound treatment. A major contribution in this regard is being made by models that enable investigation of the involvement of multiple factors in wound healing and testing new curative substances. This literature review was carried out via searches in the PubMed and Web of Science databases up to 2016. It covers skin wound healing, available models for its study (part I), the role of Nrf2 and NF-κB, substances that influence them and whether they can be used as markers (part II). Was found that in vitro assays are used for their availability but a holistic view must be established in vivo. In silico approaches are facilitating assessment of a vast amount of research data. Nfr2 and NF-κB play a crucial and reciprocal role in wound healing. Nrf2 controls repair-associated inflammation and protects against excessive accumulation of ROS while Nf-κB activates the innate immune reaction, proliferation and migration of cells, modulates expression of matrix metalloproteinases, secretion and stability of cytokines and growth factors for wound healing.
Keywords: biotest; Animals; biologické modely; proliferace buněk; přirozená imunita; NF-E2-Related Factor 2; oxidační stres; Wound Healing; Oxidative Stress; lidé; Models, Biological; Reactive Oxygen Species; kůže; faktor 2 související s NF-E2; pohyb buněk; Skin; Biological Assay; Immunity, Innate; Cell Proliferation; hojení ran; reaktivní formy kyslíku; NF-kappa B; zvířata; Cell Movement; Humans